1954
DOI: 10.1017/s0022172400027509
|View full text |Cite
|
Sign up to set email alerts
|

The carriage of Staphylococcus pyogenes var. aureus in the human nose

Abstract: Over 500 medical students have been examined for nasal carriage of Staph. pyogenes at weekly intervals over a period ranging from 3 to 12 months.Nasal carriers were classified as persistent, intermittent and occasional. Of the students, 39% were persistent or intermittent carriers in whom the staphylococcus was believed to colonize the skin of the vestibule of the nose; 42% were occasional carriers in whom the staphylococcus was only a chance inhabitant of the nares.Staph. pyogenes was isolated from the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

1957
1957
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…The Mawson results tend to confirm Sladen's proposal that there is a low incidence of occasional carriers in Antarctica, compared with temperate climates, when from 40 % (Gould & McKillop, 1954) to 60 % (Hutchinson, Green & Grimson, 1957) of a normal population will be found to carry staphylococci for short periods if observed over several months. The relative protective effect of an established coagulase-negative population in the anterior nares (Shinefield, Ribble, Boris & Eichenwald, 1963) was the only other persistent carrier of S. aureus on this trip, and he retained his type 52 strain.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The Mawson results tend to confirm Sladen's proposal that there is a low incidence of occasional carriers in Antarctica, compared with temperate climates, when from 40 % (Gould & McKillop, 1954) to 60 % (Hutchinson, Green & Grimson, 1957) of a normal population will be found to carry staphylococci for short periods if observed over several months. The relative protective effect of an established coagulase-negative population in the anterior nares (Shinefield, Ribble, Boris & Eichenwald, 1963) was the only other persistent carrier of S. aureus on this trip, and he retained his type 52 strain.…”
Section: Discussionsupporting
confidence: 72%
“…Subject 3 could be classed as an intermittent carrier, losing his nasal strain for at least 5 months and resuming with a different organism. Though some men (subjects 11, 12 and 16) did not carry their nasal strains for the complete study period, their pattern of constant carriage of organisms of similar phage type for over 9 months allows their inclusion in the category of persistent carriers (Gould & McKillop, 1954). The remaining nasal carriers were persistent carriers of S. aureus with similar phage types at each collection, except subject 13, who changed from type 52 to type 6 during June, and who carried the latter strain for the rest of the year.…”
Section: Anterior Naresmentioning
confidence: 99%
“…By including screening cultures from the throat the sensitivity of detecting colonization significantly increases and it has therefore been suggested that S. aureus screening programs should include sampling of the anterior nares as well as the throat (Mertz et al 2007). Other anatomical sites, e.g., the axilla, groin, skin and the intestinal tract, are also colonized with S. aureus (Acton et al 2009;Vento et al 2013) S. aureus nasal carriers are usually divided into three distinct groups (Gould & McKillop 1954;Kluytmans et al 1997). …”
Section: Carriage and Colonizationmentioning
confidence: 99%
“…These were considered to be carriers since swabs prior to and subsequent to admission both gave a coagulase positive staphylococcus of identical phage and antibiotic sensitivity type, and in many cases the infant also became a carrier of this strain. These cases undoubtedly belong to the class of intermittent carriers described by Gould & McKillop (1954). A population 18 K. F. ANDERSON, J. R. COULTER AND D. RUTH KEYNES was divided into three groups by these workers; the staphylococcal carriers, the non-carriers and the intermittent carriers.…”
Section: Postnatal Examinationsmentioning
confidence: 99%